RANCANG BANGUN MOTOR BLDC AXIAL FLUX MENGGUNAKAN DUA KAWAT EMAIL PADA LILITAN KUMPARAN STATOR - M Fariz Azizi; Widyono Hadi; Guido Dias Kalandro (Jurnal Arus Elektro Indonesia, 2020)
The rapid development of technology in this era of globalization has an impact on the development of electric motor technology in Indonesia. There are two types of electric motors based on the voltage source used namely DC electric motor and AC electric motor. Because the use of DC motor or AC motor has not been able to meet the needs, the use of BLDC motor (Brushless Direct Current) is a very appropriate choice. In this research, the design of BLDC Axial Flux motor used a single rotor attached to a neodymium magnet and a stator made of two email wires wrapped together. From testing the motor no-load when the source voltage is 18 V it has an input power of 4,038 W and motor speed of 1513 RPM. While when the source voltage is 24 V has an input power of 8,716 W and motor speed 1606 RPM. As for testing motors with loads when the source voltage is 24 V has an input power of 11,432 W, output power 3,579 W, efficiency 31,311%, motor speed 1098 RPM, mechanical torque 0.031 Nm, and electromagnetic torque 0.099 Nm. Coconut laying on overpressed blade roll results in the motor not being able to provide torque according to load needs, so the speed of the motor will drop, and torque increases. Besides, the greater the voltage of the source then the greater the power and speed of the motor.